Hybrid Technique for Urban Comprehensive Economic Power Evaluation Based on Probabilistic Linguistic Group Decision-Making - Fang Su; Juqiang Li; Ling Yang; Qianqian Qin (IEEE Access, 2024)
Since China’s economic reforms, the rapid rise in urbanization and industrialization has led to an increase in the number and size of cities, significantly enhancing their role in social and economic contexts. In the global arena, cities are central to economic, political, technological, and cultural advancements. As hubs for economics, politics, and education, cities crucially influence national economic cycles. A city’s comprehensive economic strength is vital in determining its status and future growth. Assessing this strength involves complex multi-attribute group decision-making (MAGDM) challenges. Techniques like Exponential TODIM (ExpTODIM) and MABAC have been utilized for such evaluations. The study introduces the probabilistic linguistic ExpTODIM-MABAC (PL-ExpTODIM-MABAC) method within probabilistic linguistic term sets (PLTSs) to better handle uncertainty in data. Additionally, the method based on the removal effects of criteria (MEREC) method helps in assigning attribute weights in PLTS contexts. A numerical example demonstrates the effectiveness of this new approach in evaluating urban economic power.